Evaluation of the forced expiration technique as an adjunct to postural drainage in treatment of cystic fibrosis. Issue 6187 (18th August 1979) - Pryor, J A; Webber, B A; Hodson, M E; Batten, J C
Abstract : Sixteen patients with cystic fibrosis were treated with conventional physiotherapy aided by an assistant. The results were compared with those produced by physiotherapy using the forced expiration technique cleared more sputum in less time than conventional physiotherapy. A sputum in less time than conventional physiotherapy. A second study showed that an assistant did not further improve the results obtained by the patient performing the forced expiration technique himself. These findings mean that patients with cystic fibrosis who have had to rely on the help of others for their home treatment may now perform more effective treatment without help. The forced expiration technique might also be helpful for patients with chronic bronchitis, asthma, or bronchiectasis.